Implementasi Program Bina Keluarga Balita (BKB) dalam Optimalisasi Tumbuh Kembang Balita di Kampung Keluarga Berkualitas Desa Sambi Kecamatan Ringinrejo Kabupaten Kediri - Rizkiana, Ayusti; Nugroho, Rivo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
The Toddler Family Development Program (BKB) exists as a form of application of out-of-school education in terms of parent education or parenting where the target is parents or families who have toddlers. The BKB program is important to implement considering that Indonesia has a high birth rate and the widespread issue of stunting which can disrupt human resource potential. This research focuses on the implementation process of the BKB Program in optimizing the growth and development of toddlers at BKB Mawar Quality Family Village Sambi Ringinrejo Kediri. The aim of this research is to determine the implementation of the BKB program in optimizing the growth and development of toddlers by examining the stages of program implementation. This research uses a qualitative approach with descriptive research type. The subjects of this research consisted of 10 organizers and members of the BKB. The data collection techniques used were in-depth interviews, observation and documentation. The data analysis techniques used are data condensation, data display, verification and conclusion. Meanwhile, to test the validity of the data, researchers use credibility, transferability, dependability and confirmability. The results of this research show that the implementation of the BKB program in optimizing the growth and development of toddlers runs optimally based on the stages of program implementation